Penelitian Kepuasan Pengguna Jasa Terhadap Pelayanan PT. Lion Air di Bandara Djalaluddin - Gorontalo - Rizki, Yuke Sri; Yuliana, Dina (Warta Penelitian Perhubungan, 2011)
Impravement of passenger service at PT.Lion Air must be considered in order to meet desires and expectations of airlines services users. Research of Satisfaction Service User of Lion Air had taken sampling at the Djalaluddin - Airport Gorontalo. The number of sampling was 200 pasangers. The objective of the study is to determine the level of air transport services by PT. Lion Mentari Air during pre flight, in flight and post flight. Analysis method used the quadrant analysis by comparing the satisfaction value and expectations of the airline passenger. The study results showed that the attributes should be further enhanced its performance in order to satisfy the passengers is on time departure service, speed of baggage claim, and complaint handling goods I luggage (In the event of loss I damage).Keywords: services, satisfaction, airlines, passenger.